ChemInform Abstract: A Diversity Oriented One‐Pot Synthesis of Novel Iminosugar C‐Glycosides. Issue 20 (20th May 2014) - Senthilkumar, Soundararasu; Prasad, Sure Siva; Kumar, Ponminor Senthil; Baskaran, Sundarababu
Abstract The reaction proceeds with complete regio‐ and stereoselectivity.